The use of electrochemical noise in the study of nanometric coatings - Gaona Tiburcio, Citlalli; López Cazares, Irene; Cabral Miramontes, José Ángel; Zambrano Robledo, Patricia del Carmen; Uruchurtu Chavarín, J. (InTech, 2014)
This chapter presents the study and analysis of the application of nanometric films of SS 304 and nanometric Al/Cr and Cr/Al bilayers deposited on different aluminum and steel alloys by magnetron sputtering and DC sputtering. The materials were characterized by scanning electron microscopy (SEM) and electrochemical noise in order to consider their application as high corrosion resistance coatings. The corrosion behavior of the films was studied using a NaCl aqueous solution (3.5 wt%).